2009
DOI: 10.3324/haematol.2009.017392
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-4 and CD36 are implicated in the abnormal adhesiveness of sickle cell SAD mouse erythrocytes to endothelium

Abstract: BackgroundAbnormal adhesiveness of red blood cells to endothelium has been implicated in vaso-occlusive crisis of sickle cell disease. The present study examined whether the SAD mouse model exhibits the same abnormalities of red blood cell adhesion as those found in human sickle cell disease. Design and MethodsThe repertoire of adhesive molecules on murine erythrocytes and bEnd.3 microvascular endothelial cells was determined by flow cytometry using monoclonal antibodies or by western blotting. Adhesion was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] Binding of both red cells and leukocytes to endothelial selectins has been proposed to have a critical role in SCD VOC. 13,[15][16][17] Endothelial E-selectin expression is upregulated by inflammatory cytokines and can become a target, along with P-selectin, for leukocyte adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Binding of both red cells and leukocytes to endothelial selectins has been proposed to have a critical role in SCD VOC. 13,[15][16][17] Endothelial E-selectin expression is upregulated by inflammatory cytokines and can become a target, along with P-selectin, for leukocyte adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ICAMs can also generate soluble ICAMs (sICAM‐1), via ectodomain shedding, which is generally considered to be associated with endothelial injury or inflammation in vivo . These sICAM‐1 can compete for ligand binding sites with native mICAMs present on the cell surface and thus reduce cell adhesion . Thus, in this study, we selected ICAM‐1 as a marker to explore the relationship among the expression of ICAM‐1, pore size of the micropore and cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, Trinh-Trang-Tan et al, using sickle cell SAD mice, showed recently that erythrocyte CD36 contributes to the increased SAD RBC adhesion, while endothelial CD36 is not indispensable. 36 The issue is complex because CD36 is less strongly expressed on RBC from SAD than wild-type mice. Thus a potential CYinduced decrease of CD36 at the surface of HPMEC might not directly correlate with decreased adhesive properties in inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%